Azobenzene Photoswitch for Isomerization‐Dependent Cancer Therapy via Azo‐Combretastatin A4 and Phototrexate. (6th July 2020) - Mulatihan, Dinaer; Guo, Tao; Zhao, Yanjun
Abstract: The adverse effects of chemotherapeutic drugs to healthy organs/cells greatly limit their clinical efficacy and patient compliance. The unique behavior of azobenzene photoswitch offers a remarkable tool to address the side effects of chemotherapeutic drugs. The azobenzene moiety has been integrated within some chemotherapeutic drugs to realize photo‐triggered activation of drug cytotoxicity. However, the clinical translation of these agents has been facing a few barriers. In this short review, we present our viewpoints on potential solutions to address the following challenges associated with azobenzene‐based photoswitchable chemotherapeutic drugs, including poor tissue penetration of light, hypoxia‐induced drug degradation in solid tumor and the autonomous cis‐trans relaxation. Abstract : Azo‐combretastatin A4 (Azo‐CA4) and phototrexate (PTX) display isomerization‐dependent cytotoxicity. The "trans" isomer is thermodynamically stable and inactive, whereas the "cis" isomer is active, but thermodynamically unstable. However, the in vivo application of these photoswitchable agents has been challenged by limited tissue penetration of ultraviolet light, hypoxia‐induced drug degradation in tumor microenvironment and autonomous "cis‐trans" reverse isomerization. This review discusses possible solutions to address these challenges.